α-Tocopherol and β-carotene concentrations in feed, colostrum, cow and calf serum in Swedish dairy herds with high or low calf mortality - Maria Torsein; Ann Lindberg; Catarina Svensson; Sören Krogh Jensen; Charlotte Berg; Karin Persson Waller (Acta Veterinaria Scandinavica, 2018)
Abstract Background A study of herd-level risk factors for calf mortality in large Swedish dairy herds showed low serum concentrations of α-tocopherol and β-carotene in 1–7 day old calves to be more common in high mortality herds. Therefore, we aimed to investigate if calf mortality risk at herd level is associated with concentrations of α-tocopherol and/or β-carotene at individual level in feed, colostrum, cow and calf serum, while controlling for herd level covariates. Inclusion criteria were affiliation to the Swedish official milk recording scheme, herd size of ≥ 120 milking cows/year, calf mortality risk (day 1–90) of at least 6% (high mortality; HM) or less than 1% (low mortality; LM) and located within one of two regions in southern Sweden. This cross-sectional study was performed in 2010 in 19 (nHM = 9; nLM = 10) dairy herds. Questionnaires were used to collect information about feed and routines for colostrum feeding. Feed (n = 57), colostrum (n = 162), cow serum (n = 189) and calf serum samples (n = 187) were collected and analysed for α-tocopherol and β-carotene. Other analyses e.g. total serum protein, fat content, and total solids in colostrum were also performed. Linear regression models with vitamin concentrations in feed, colostrum, cow and calf serum as outcome were performed. Results Calves in HM herds had lower concentrations of α-tocopherol in serum than calves in LM herds, but the effect depended on total protein status in serum of the calf (P = 0.036). Calves from herds that fed transition milk for 3 days or more had higher α-tocopherol concentrations in serum than calves from herds feeding transition milk up to 2 days (P = 0.013). Fat percentage in colostrum was positively associated with α-tocopherol (P < 0.001) and β-carotene concentrations in colostrum (P < 0.001). A diet containing ≥ 20% (in kg dry matter) maize silage of the total ration was negatively associated with β-carotene concentration in cow serum (P = 0.001). Conclusions High calf mortality risks were associated with lower concentrations of α-tocopherol in calf serum for calves with failure of passive transfer. Feeding transition milk longer was associated with higher concentrations of α-tocopherol in calf serum. In HM herds, evaluation of the calves’ α-tocopherol status is recommended.